A Correlation Between Proteinuria, Enzymuria And Kidney Histopathological Changes During Early Renal Damage Induced By Gentamlcln - Abdul Karim, Sairah (2004)
This study was carried out to determine the correlation between urine proteins and urinary enzyme markers, aspartate aminotransferase (AST), yglutamyl transferase (y-GT) and alkaline phosphatase (ALP) and tissue histopathological changes during early renal damage induced by gentamicin. Fifty five Sprague-Dawley rats, aged 7-8 weeks old were divided into two groups. One group of ten rats served as controls and forty-five rats were treated with gentamicin intraperitoneally to induce renal damage. Twenty four hour urine samples were collected daily for 3 days. On the third day, blood was withdrawn through cardiac puncture and kidney tissues from sacrificed rats were taken for histopathological analysis. Urine proteins were separated by sodium dodecyl sulphate - polyacrylamide gel electrophoresis (SDSPAGE). Concentration of urine proteins, enzymes, serum urea nitrogen (BUN) and creatinine were analysed using a chemistry analyser. The SDS-PAGE of urine proteins showed that proteinuria in gentamicin-treated rats consisted primarily of protein with low molecular weight. The separated urine proteins were mainly located in the molecular weight range of 10 to > 70 kDa. An extra protein band with molecular weight estimated to be approximately 11 kDa was also detected in the gentamicin-treated group and suggested to be an indicator of early renal disease. The electrophoretic patterns of urine proteins also demonstrated that the type of proteins leaking into urine had also provided some insight on the location and degree of renal injury. High urine enzymes concentrations specifically ALP had also reflected that the onset of injury was in the renal proximal tubular cells. This was confirmed by renal tissue histopathological evidences. Each parameter showed a high grading in gentamicin-treated group. Grade 3 cytoplasmic vacuolization (31%), grade 3 tubular dilatation (33.3%) and grade 3 cell detachment (33.3%) were the most prominent morphological changes in that group. BUN and serum creatinine did not show any obvious difference between the two groups. In conclusion, the elevated concentrations of low molecular weight urine proteins and urine enzymes appeared to be useful indicators for early renal damage as their elevation occurred before the BUN and serum creatinine produced any change.